Dendritic Mesoporous Silica Nanoparticle Adjuvants Modified with Binuclear Aluminum Complex: Coordination Chemistry Dictates Adjuvanticity. (19th October 2020) - Yang, Yang; Tang, Jie; Song, Hao; Yang, Yannan; Gu, Zhengying; Fu, Jianye; Liu, Yang; Zhang, Min; Qiao, Zhen‐An; Yu, Chengzhong
Abstract: Aluminum‐containing adjuvants used in vaccine formulations suffer from low cellular immunity, severe aggregation, and accumulation in the brain. Conventional aluminosilicates widely used in the chemical industry focus mainly on acidic sites for catalytic applications, but they are rarely used as adjuvants. Reported here is an innovative "ligand‐assisted steric hindrance" strategy to create a high density of six‐coordinate VI Al−OH groups with basicity on dendritic mesoporous silica nanoparticles as new nanoadjuvants. Compared to four‐coordinate IV Al‐modified counterparts, VI Al−OH‐rich aluminosilicate nanoadjuvants enhance cellular delivery of antigens and provoke stronger cellular immunity. Moreover, the aluminum accumulation in the brain is more reduced than that with a commercial adjuvant. These results show that coordination chemistry can be used to control the adjuvanticity, providing new understanding in the development of next‐generation vaccine adjuvants. Abstract : A new class of mesoporous aluminosilicate adjuvants is created by controlling the surface coordination chemistry, which further adjusts the adjuvanticity. Nanoadjuvants modified with a binuclear octahedral aluminum‐acetate complex, with a high density of six‐coordinate VI Al−OH species and Brønsted basicity, show superior performance compared to counterparts modified with four‐coordinate IV Al species with Brønsted acidity and a commercial product.